Japanese Orange Fly, Bactrocera tsuneonis (Miyake) (Insecta: Diptera: Tephritidae) - Howard V. Weems; Thomas R. Fasulo (EDIS)
This fruit fly is one of the most important pests of citrus in Japan. There have been no interceptions of the Japanese orange fly in the United States, probably due in a large part to the protection provided by a U.S. embargo of long standing against citrus from the orient. There have been some efforts recently to affect the removal of this embargo in order that citrus from Japan might be exported to the U.S. If this were to be done, the danger of introducing the Japanese orange fly into the U.S. would be greatly increased. This revised 2-page fact sheet was written by H. V. Weems, Jr. and T. R. Fasulo, and published by the UF Department of Entomology and Nematology, March 2012.